MeCP2 interacts with chromosomal microRNAs in brain. Issue 12 (2nd December 2017) - Khan, Abdul Waheed; Ziemann, Mark; Rafehi, Haloom; Maxwell, Scott; Ciccotosto, Giuseppe D.; El-Osta, Assam
ABSTRACT: Although methyl CpG binding domain protein-2 (MeCP2) is commonly understood to function as a silencing factor at methylated DNA sequences, recent studies also show that MeCP2 can bind unmethylated sequences and coordinate gene activation. MeCP2 displays broad binding patterns throughout the genome, with high expression levels similar to histone H1 in neurons. Despite its significant presence in the brain, only subtle gene expression changes occur in the absence of MeCP2. This may reflect a more complex regulatory mechanism of MeCP2 to complement chromatin binding. Using an RNA immunoprecipitation of native chromatin technique, we identify MeCP2 interacting microRNAs in mouse primary cortical neurons. In addition, comparison with mRNA sequencing data from Mecp2 -null mice suggests that differentially expressed genes may indeed be targeted by MeCP2-interacting microRNAs. These findings highlight the MeCP2 interaction with microRNAs that may modulate its binding with chromatin and regulate gene expression.